Adipose Tissue Expression of Gelatinases in Mouse Models of Obesity - Lijnen, H. R.; Maquoi, E.; Holvoet, P.; Mertens, A.; Lupu, F.; Morange, P.; Alessi, M. C.; Juhan-Vague, I. (Thrombosis and Haemostasis, 2001)
Following the observation by Brown et al. (Am J Physiol 1997; 272: C937-49) that primary rat adipocytes in culture secrete gelatinase A (MMP-2), we have evaluated gelatinase expression in adipose tissue with the use of mouse models of obesity. Wild-type mice were kept on a standard fat diet (SFD) or on a high fat diet (42% fat, HFD) and genetically obese db/db mice were kept on SFD; gonadal and subcutaneous fat pads were removed and analysed ex vivo. These studies revealed that: 1) the HFD induced adipocyte hypertrophy; 2) after 32 weeks, significantly higher levels of 70 kDa (p <0.05) and 65 kDa proMMP-2 (p < 0.01) were observed in extracts of gonadal fat pads of mice on HFD; 3) the contribution of active MMP-2 to the total level was comparable in SFD and HFD groups (20 to 30%); and 4) gelatinase B (MMP-9) was not consistently detected. These findings were confirmed by gelatin zymography and by mRNA determination using competitive RT-PCR. The presence of MMP-2 in the adipose tissue was confirmed immunologically and its localization in adipocytes revealed by immunogold electron microscopy. The potential functional role of MMP-2 in adipose tissue remains to be determined.
Keywords: Obesity; matrix metalloproteinases; gelatinase